Complexity in Syntax with the Use of an Adverbial Clause of Concession - Matšitso Eugenia Morato-Maleke; Lipuo Motene (Journal La Edusci, 2021)
The present study explores the use of adverbial clause of concession as a syntactic complexity measure among the National University of Lesotho (NUL) students. The research subjects were NUL fourth year students across the seven faculties namely, the Faculty of Agriculture (FOA), the Faulty of Education (FOE), the Faculty of Health Sciences (FOHS), the Faculty of Humanities (FOH), the Faculty of Law (FOL), the Faculty of Social Sciences (FOSS) and the Faculty of Science and Technology (FOST). Data was collected from their past examination papers (2016/2017). This paper employed the interpretivist paradigm and has analysed the data qualitatively. The study has also employed the descriptive and case study designs. The students’ continuous writing was the focus of this study since Transformational Generative Grammar (TGG) and Cognitive Grammar (CG) are the theoretical frameworks which the present paper was based on and therefore require continuous writing. The findings of the present paper reveal that NUL students have a relatively low level of syntactic complexity in their writing as shown by how they used adverbial clauses of concession. The study therefore concludes that NUL students have a moderately low level of syntactic complexity demonstrated by how they used this feature.